Synthesis, Growth, Spectroscopic and Thermal Studies of Organic Adduct of L-Alaninium Tartrate Single Crystal - Ramesh Kumar, P.; Kumararaman, S.; Sagayaraj, P. (Asian Journal of Chemistry, 2010)
Organic non-linear optical materials are potential candidates for frequency mixing, electrooptic modulation, optical parametric oscillation optical by stability etc., due to the large optical non-linearity, low cutoff wavelength, short response time and high thresholds for laser power. In the present investigation, bulk crystal of L-alaninium tartrate, an organic adduct of L-tataric acid was grown by slow solvent evaporation technique. The grown crystal was subjected to single crystal X-ray diffractometry (XRD) to estimate the crystal structure and space group and its morphology was also studied. The optical property of the crystal was investigated using UVvis- NIR. The functional groups were identified by the FTIR spectral analysis. The thermal stability of the crystal was estimated by TG/DTA.